2005
DOI: 10.1128/jcm.43.3.1480-1483.2005
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Peritonitis Caused by Pasteurella multocida Capsular Type F in Calves

Abstract: A fatal case of atypical septicemia of pasteurellosis in veal calves is described. The causative organism was identified as a multiresistant Pasteurella multocida capsular type F isolate. The outbreak was characterized by fibrinous peritonitis and mortality, which are hitherto unreported features of P. multocida capsular type F infections. CASE REPORTSMale Holstein-Friesian calves (age, 2 weeks) were housed in individual wooden straw-bedded boxes. They were fed a milk replacer diet twice a day. The diet was su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 17 publications
1
12
1
Order By: Relevance
“…However, we detected a lower incidence of this type than in a recent study form Hungary (Kardos and Kiss, 2005). Catry et al (2005) reported this type to be more frequently detected in various mammalian species. Other capsular types were not found among our strains.…”
Section: Resultscontrasting
confidence: 71%
“…However, we detected a lower incidence of this type than in a recent study form Hungary (Kardos and Kiss, 2005). Catry et al (2005) reported this type to be more frequently detected in various mammalian species. Other capsular types were not found among our strains.…”
Section: Resultscontrasting
confidence: 71%
“…Jaglic et al (2004) previously described the presence of P. multocida capsular type F isolates in rabbits. Capsular type F isolates had been traditionally associated with fowl cholera in birds, but in the past few years they have been occasionally reported in other hosts, including cattle, sheep, and pigs, in different parts of the world (Ewers et al, 2006;Bethe et al, 2009;Davies et al, 2003;Catry et al, 2005). Most of the rabbit capsular type F isolates (19/25) were positive only for the pfhA gene with a statistically significant association (P < 0.05).…”
Section: Tablementioning
confidence: 90%
“…Sepsis is regarded as a sporadic disease, but massive epidemics of sepsis can occur with virulent bacteria like Salmonella spp. (especially host adapted species like Salmonella Dublin), Histophilus somni, Mannhaemia haemolytica or Pasteurella multocida, especially in young animals (Catry et al, 2005;Mahu et al, 2015;McFadden et al, 2011). In the immunocompromised host, sepsis is more likely to occur.…”
Section: Sepsis Incidence Etiology and Risk Factors In Cattlementioning
confidence: 99%